Prevalence of specific neutralizing antibodies against Sendai virus in populations from different geographic areas: Implications for AIDS vaccine development using Sendai virus vectors - Hara, Hiroto; Hironaka, Takashi; Inoue, Makoto; Iida, Akihiro; Shu, Tsugumine; Hasegawa, Mamoru; Nagai, Yoshiyuki; Falsey, Ann R.; Kamali, Anatoli; Anzala, Omu; Sanders, Eduard J.; Karita, Etienne; et al. (Human vaccines, 2011)
A Sendai virus (SeV) vector is being developed for delivery of an HIV immunogen. SeV is not known to cause disease in humans. Because it is genetically and antigenically related to human parainfluenza virus type 1 (hPIV-1), it is important to determine whether pre-existing hPIV-1 antibodies will affect immune responses elicited by a SeV vector-based vaccine. To quantify SeV neutralizing antibodies (NAb) in human serum, a sensitive virus neutralization assay was developed using a SeV vector encoding green fluorescent protein. Samples from 255 HIV-uninfected subjects from Africa, Europe, United States, and Japan, as well as from 12 confirmed hPIV-1-infected patients, were analyzed. SeV NAb titers did not vary significantly after serum was treated with receptor-destroying enzyme, indicating that non-specific hemagglutination inhibitors did not affect the assay sensitivity. A significant correlation was observed between hPIV-1 ELISA and SeV NAb titers. SeV NAb were detected in 92.5% subjects with a median titer of 60.6 and values ranging from 5.9- 11,324. The majority had titers